2015
DOI: 10.1111/efp.12243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture conditions on medium discoloration and mycelial growth of Dothistroma septosporum

Abstract: Dothistroma septosporum is one of the most damaging fungi-attacking pines wherever they are grown. Specific symptoms on pine include the formation of red bands on needles and the appearance of which is attributed to dothistromin, a toxin produced by this pathogen. Many reports have suggested that such red bands do not appear in all infections, although the cause of this phenomenon is unclear. When grown in vitro, some strains of D. septosporum cause an intense blue, rather than red, coloration of the medium. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…The variation in agar coloration during Dothistroma spp. growth in culture has been mentioned by other authors, too (Kowalski, Nawrot‐Chorabik, Grad, & Leszczyński, 2016; Mullett & Barnes, 2012). The colour of red bands in necrotic needle lesions depends mainly on the production and accumulation of red toxin, dothistromine, but can sometimes also occur due to the metabolic products of other fungi inhabiting the same needles (Kowalski et al., 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The variation in agar coloration during Dothistroma spp. growth in culture has been mentioned by other authors, too (Kowalski, Nawrot‐Chorabik, Grad, & Leszczyński, 2016; Mullett & Barnes, 2012). The colour of red bands in necrotic needle lesions depends mainly on the production and accumulation of red toxin, dothistromine, but can sometimes also occur due to the metabolic products of other fungi inhabiting the same needles (Kowalski et al., 2016).…”
Section: Discussionmentioning
confidence: 78%
“…The colour of red bands in necrotic needle lesions depends mainly on the production and accumulation of red toxin, dothistromine, but can sometimes also occur due to the metabolic products of other fungi inhabiting the same needles (Kowalski et al., 2016). During in vitro experiments, it was found that the colour of the secreted pigment is not a constant character of the fungal isolate, but usually depends on the growth temperature and pH of the medium (Kowalski et al., 2016). Lower temperature and lower pH stimulated the production of the blue pigment.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Boron et al (2016) is an exemplar of the type of detailed country-level study that was performed using molecular expertise gained in a DIAROD training school and shows that D. septosporum has spread around most of Poland since the first record of its appearance in 1990. The work of Kowalski et al (2016) highlights the phenotypic plasticity and diversity of D. septosporum isolates in culture and shows there is a lot more to learn about secondary metabolism in this pathogen and the influence of other fungi in the host needle. In this issue, Siziba et al (2016) take this finding one step further by describing the development of microsatellite markers for D. pini and use of these markers for a population study in which isolates from France were found to be genetically diverse.…”
Section: Special Issue On Dothistromamentioning
confidence: 99%
“…Storage of fungal cultures from such studies is extremely important; in this issue, Fraser et al (2016c) outline a thorough study of six storage methods and make recommendations about the best methods to retain culture viability in the long term. The work of Kowalski et al (2016) highlights the phenotypic plasticity and diversity of D. septosporum isolates in culture and shows there is a lot more to learn about secondary metabolism in this pathogen and the influence of other fungi in the host needle. With a focus on environmental effects, the review by Woods et al (2016) assesses the relationship between DNB, weather factors and climate, to gain a clearer picture of possible underlying causes of the recent increase in disease range and severity.…”
Section: Special Issue On Dothistromamentioning
confidence: 99%
“…This species is a member of the fungal family Mycosphaerellaceae, and is phylogenetically related to the genera Stromatoseptoria , Hyalocercosporidium and Dothistroma (Videira et al., 2017). When these fungi are cultured in vitro , the pigment produced within their mycelia varies according to growth substrate, and might be used as a diagnostic trait and/or may provide additional information regarding phylogenetically related fungi (Saparrat et al., 2009; Kowalski et al., 2016). Aguilera-Cogley et al.…”
Section: Introductionmentioning
confidence: 99%